EVALUATION OF VILLAGE GOVERNMENT COOPERATION AND THE VILLAGE CONSULTATIVE BODY IN THE VILLAGE DEVELOPMENT PLANNING PROCESS - Sri Yulianty Mozin; Ely Ibrahim; Hartakni Hartawan (Governance: Jurnal Ilmu Administrasi Publik, 2021)
The purpose of this research is: (1) find out and analyze the evaluation of Village Government cooperation and BPD in the village development planning process in the Pinolsian District, South Bolaang Mongondow Regency. (2) find out and analyze the factors that determine the cooperation between the Village Government and BPD in the village development planning process in the Pinolsian District, South Bolaang Mongondow Regency. This research is qualitative research with a qualitative descriptive case study approach to study, analyze, and decrypt. Research result: (1) Preparation and stipulation of Village RPJM (Reviving the Village Medium-Term Development Plan) of all villages in Pinolosian District on time; (2) The preparation and stipulation of the Village RKP 2019 for all villages in the Pinolosian District was not on time; (3) The preparation and stipulation of the Village APB 2019 for all villages in the Pinolosian District was not on time; (4) Agreement between the Village Government and the BPD regarding the 2019 Ranperdes Village APB for all villages in the Pinolosian District was not on time; (5) The Village APB 2019 determination for all villages in the Pinolosian District was not on time; There are 7 (seven) villages for which the village APB determination is not following Permendagri 20/2018; (7) The factors that determine the cooperation between the Village Government and the BPD in the village development planning process, namely: Policy, Budget, Human Resources, Facilities, and Infrastructure, and Communication.